Translation and Validation of the Standardized Cosmesis and Health Nasal Outcomes Survey in Dutch - Pingnet Laura; Verkest Valérie; Saltychev Mikhail M.; Most Sam P.; Declau Frank (Koninklijke Belgische Vereniging voor ORL Gelaat en Halschirugie, 2022)
Objective: The Standardized Cosmesis and Health Nasal Outcomes Survey is a validated instrument for patients undergoing rhinoplasty surgery. The aim of this study was to validate a Dutch-language version of the Standardized Cosmesis and Health Nasal Outcomes Survey.
Methods: The Standardized Cosmesis and Health Nasal Outcomes Survey was translated and back-translated and 10 Dutch-speaking rhinoplasty patients were interviewed to evaluate the translation. The translated version was administered to 25 rhinoplasty patients (cases) and 25 controls at 2-week intervals. The internal consistency, test–retest reliability, and factor structure of Standardized Cosmesis and Health Nasal Outcomes Survey were measured.
Results: Both the obstructive domain of the Standardized Cosmesis and Health Nasal Outcomes Survey and the cosmetic domain showed a high internal consistency, alpha 0.94 and 0.95, respectively. The Standardized Cosmesis and Health Nasal Outcomes Survey was reliable showing very strong test–retest correlations of 0.93 for Standardized Cosmesis and Health Nasal Outcomes Survey-obstructive domain and 0.94 for Standardized Cosmesis and Health Nasal Outcomes Survey-cosmetic domain, respectively. The Wilcoxon rank-sum test showed a significant difference between cases and controls for the Standardized Cosmesis and Health Nasal Outcomes Survey-cosmetic domain (P =.0001) but not for the Standardized Cosmesis and Health Nasal Outcomes Survey-obstructive domain (P =.14). Exploratory factor analysis showed unidimensionality for both the Standardized Cosmesis and Health Nasal Outcomes Survey-cosmetic domain and the Standardized Cosmesis and Health Nasal Outcomes Survey-obstructive domain.
Conclusion: The Standardized Cosmesis and Health Nasal Outcomes Survey was successfully translated, culturally adopted, and validated for its use in a Dutch-speaking population of rhinoplasty patients.